2022
DOI: 10.3390/healthcare10101809
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Artery Disease Causes More Harm to Patients than COVID-19

Abstract: Background: To optimize our strategic planning, we aimed to investigate the impact of the COVID-19 pandemic on the treatment of patients with peripheral artery disease (PAD) at our tertiary care hospital. Methods: We performed a retrospective single-center cohort study. In total, 1210 patients were included: 611 patients admitted between March and December 2020, compared to retrospective data from 599 patients from the same period in 2019. Results: Emergency admissions involving patients with advanced stage PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This reduction in follow-up most likely contributed in a signi cant way to the deterioration of PAD in these patients which eventually lead to them requiring more revascularisation procedures during the pandemic. Indeed a few studies report that patients who presented to hospital with PAD during the pandemic had more severe disease on average compared to pre-pandemic times and required more advanced interventions or even amputations (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in follow-up most likely contributed in a signi cant way to the deterioration of PAD in these patients which eventually lead to them requiring more revascularisation procedures during the pandemic. Indeed a few studies report that patients who presented to hospital with PAD during the pandemic had more severe disease on average compared to pre-pandemic times and required more advanced interventions or even amputations (9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of trends in procedure volume with respect to lockdown periods, this study found a decline in revascularisation procedures during lockdown periods lasting over 30 days, however, over the longer term, there was an overall increase in revascularisation procedures performed during the pandemic. Previous studies have noted a decline in vascular surgery procedures during the pandemic compared to pre‐pandemic times, but none have investigated the correlation between procedure volume and lockdown periods or the nature of lockdowns [9–12]. Future studies analysing this correlation could aid in developing lockdown strategies that minimise disruptions to healthcare services.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in follow-up most likely contributed in a significant way to the deterioration of PAD in these patients which eventually lead to them requiring more revascularisation procedures during the pandemic. Indeed a few studies report that patients who presented to hospital with PAD during the pandemic had more severe disease on average compared to pre-pandemic times and required more advanced interventions or even amputations [9][10][11][12]. Another contributing factor to the increase in revascularisations during the pandemic is a general decline in patient health during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be explained by worse accessibility to diagnostic procedures and therefore lower possibilities for proper vascular disease diagnosis due to pandemic restrictions. Kasiri et al [76] presented an increased number of emergency admissions with unsuccessful revascularization attempts requiring limb amputation, due to pandemic lockdown protocols which limited ability for accurate planned diagnosis.…”
Section: Discussionmentioning
confidence: 99%